2018
DOI: 10.1007/s13187-017-1317-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Educational Intervention Based on Health Belief Model and Social Support on Promoting Skin Cancer Preventive Behaviors in a Sample of Iranian Farmers

Abstract: Skin cancer is one of the most common cancers in Iran. Farmers are exposed to the sun's ultraviolet radiation due to their job and are susceptible to skin cancer. The aim of this study is to survey the effect of educational intervention based on health belief model and social support on promoting skin cancer preventive behaviors in farmers of Fasa City, Fars province, Iran. In this quasi-experimental study, 200 farmers (100 in experimental group and 100 in control group) in Fasa City, Fars, Iran, were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
11
18
0
Order By: Relevance
“…This finding is consistent with the results of (5). Perceived severity also directly affects protective behavior, which is also consistent with previous studies (23)(24)(25)(26). The influence of self-efficacy on behavioral intention is justified by the consideration that when respondents perceive that they have the ability to take preventive measures, they are expressing mental readiness to participate in coping behaviors.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with the results of (5). Perceived severity also directly affects protective behavior, which is also consistent with previous studies (23)(24)(25)(26). The influence of self-efficacy on behavioral intention is justified by the consideration that when respondents perceive that they have the ability to take preventive measures, they are expressing mental readiness to participate in coping behaviors.…”
Section: Discussionsupporting
confidence: 84%
“…The results of a study by Maseudi et al showed a significant difference between the scores of the construct of perceived vulnerability in the intervention group that was measured before and 2 months after the intervention (19). Our findings are also consistent with the results of a study by Jeihooni and Rakhshani entitled "the effect of educational intervention based on health belief model and social support on promoting skin cancer preventive behaviors in a sample of Iranian farmers" (20). This is probably due to the increase in the farmers' sensitivity to the risk of exposure to sunlight after educational program; because of the intervention, they might have found themselves at risk for diseases caused by sunlight, including skin cancer, which occurs due to climate change such as changes in the thickness of the ozone layer.…”
Section: Discussionsupporting
confidence: 91%
“…Twenty‐two studies focused on education programmes. Four of the six intervention studies assessing the influence of particular educational programmes on sun‐related knowledge found a significant improvement …”
Section: Resultsmentioning
confidence: 99%
“…Four studies assessed sun‐related attitudes, of which three found significant differences in the sun risk attitude and perceived sun damage susceptibility . Sixteen studies found a significant protective behavioural changes and two studies reported significant changes in the intention to change sun protection behaviour …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation